Caracterização morfológica de adultos de Nusalala tessellata (Gerstaecker, 1888) (Neuroptera, Hemerobiidae) - Lara,Rogéria Inês Rosa (2002)
Morphologic characterization of adult of Nusalala tessellata (Gerstaecker, 1888) (Neuroptera, Hemerobiidae). Adult of N. tessellata is redescribed based on morphological characters. 533 specimens were collected in São Paulo state in plantations of citrus (Santa Rosa de Viterbo), soybean (Nuporanga), cotton (Ribeirão Preto) and corn (Ribeirão Preto and Jaboticabal). Some other additional specimens collected on Sorghum bicolor (Lavras-MG) and Ilex paraguariensis (São Mateus do Sul, Cascavel-PR) were also studied. Illustrations obtained by SEM are given by first time.